Architectural accessibility, physical handicap and the right to education (Olhar de Professor, 2021)
This paper presents the results of a study that aims to analyze architectural accessibility in municipal schools in Pinhais in the state of Paraná, under the perspective of the right to quality education and the existing regulations. Four schools are investigated through an observation script comprising 122 items and interviews with the principals. The surroundings of the school, parking area, entrances, classrooms, library or reading room, computer lab, cafeteria, restrooms, reception, drinking fountain, space for sports practice, park, and patio, are some of the spaces and furniture observed. Based on the theoretical background by Crahay (2000) and Lucas (2001), it was possible to identify the inequality maintenance mechanisms (DEM), as well as the need to discuss the adaptation of spaces, educational indicators and the broadening of an educational policy aimed at accessibility.
Keywords: Education. Architectural accessibility. Inclusion.